2013
DOI: 10.1016/j.physbeh.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of housing variables on the development of stress-sensitive behaviors in the rat

Abstract: • Laboratory bedding material inuences developmental programming of rats.• Bedding material during early life can alter stress sensitive measures in adulthood.• Corncob bedding during sensitive periods decreases adult measures of anxiety.• Bedding material during adulthood does not affect adult anxiety-like behavior. Diverse environments early in mammalian life can have profound inuences on the physiology and behavior of developing offspring. Environmental factors can inuence offspring development directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
3
15
0
2
Order By: Relevance
“…In the present and previous study(Marques-Carneiro et al, 2014) most parameters measured inWistars sometimes differed from NECs and sometimes from GAERS, while the consequences of early life environment should be rather consistent, and thus concordant(Weaver et al, 2006;Masís-Calvo et al, 2013;Sakhai et al, 2013). This indicates that early life environment cannot be the only cause of the differences recorded in this study.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…In the present and previous study(Marques-Carneiro et al, 2014) most parameters measured inWistars sometimes differed from NECs and sometimes from GAERS, while the consequences of early life environment should be rather consistent, and thus concordant(Weaver et al, 2006;Masís-Calvo et al, 2013;Sakhai et al, 2013). This indicates that early life environment cannot be the only cause of the differences recorded in this study.…”
supporting
confidence: 69%
“…GAERS and NECs were born and raised under the exact same environmental conditions while Wistars were provided by a commercial breeder. Therefore, despite a general respect of strict national and international guidelines, which contributes to level rearing conditions, it cannot be excluded that gestation and early postnatal environmental conditions may have differed between Wistars and the two genetic groups in a way that could partly impact on the herein reported differences (Weaver et al, 2006;Masís-Calvo et al, 2013;Sakhai et al, 2013 …”
Section: Limitations Of the Studymentioning
confidence: 96%
“…More recent observations have demonstrated that the effects of corncob use extend beyond sexual and aggressive behavior. Male rats housed on corncob bedding have reduced anxiety-like behavior and decreased slow-wave sleep compared to rats raised on wood pulp based bedding [104, 105]. In addition, corncob bedding also reduced sex differences in social withdrawal behavior following social defeat stress [106].…”
Section: Environmental Estrogens As Behavioral Disruptorsmentioning
confidence: 99%
“…The impact of housing in an enriched environment versus a barren cage on normal neural development is widely known (e.g. Rosenzweig and Bennett, 1996;Sakhai et al, 2013). Another clear example is the reversal of memory deficits in mice with a depletion of the n-methyl-d-aspartate receptor in the CA1 region of the hippocampus observed when these mice were housed under enriched circumstances (Rampon et al, 2000).…”
Section: Limitations Of Housing and Environmental Conditionsmentioning
confidence: 99%